Identifying the Stakeholders and Sustainability Indicators for Sonok Breeding System - Nugroho, Tristianto; Maharani, Dyah; Widi, Tri Satya Mastuti (2019)
Sonok contest is a cultural event involving cattle in Madura Island, Indonesia. Sonok breeding strategy and event are unique since they involve only the female cattle. Many stakeholders participate in the value chain. This study was aimed to identify stakeholders in Sonok breeding system and to determine sustainability issues and indicators. The study was conducted by a literature review and discussion with experts. The procedures are consisted of 3 phases, including problem definition, identifying and analysis relevant stakeholders, then determining Economic, Ecological, and Societal (EES) relevant issues. Next step, the EES issues were translated into sustainability indicators. As a result, there were two stakeholders, primary and secondary stakeholders. Primary stakeholders consisted of cultural groups, farmers, and policymakers. Secondary stakeholders consisted of local government, inseminator/veterinarians, butchers, and traders. Several issues were elaborated at the farm level. Economically benefit, manure use and human well-being were important issues. Selected sustainability indicators were farmer income, cattle growth and reproduction, manure production, feed availability, farm size, cultural value, and cattle/human health and disease. According to the result, the present stakeholders and sustainability indicators need to tested and confirmed with data to assess the sustainability of Sonok breeding systems.